Christliche Publizistik im Wandel - Zeltner Pavlovic, Irena (Pastoraltheologie, 2017)
In reference to publications of the Christian Media and Communication Studies programme at the University of Erlangen in the past 50 years, the article shows how the theory has changed from an applied action science towards a communication science. Furthermore, the development of its character as an interdisciplinary and transdisciplinary science, as a social science, and as a hybrid between application and theory, is suggested by the author.